(untitled) (Web of Teachers: Inderscience Research, 2025)
This article explores innovative methodologies in foreign language education, focusing on contemporary strategies for teaching English to elementary school students. Drawing upon recent research and expert opinions, it examines the efficacy of various approaches and their implications for language acquisition at the primary education level. The discussion includes the integration of technology, task-based learning, and the importance of cultural context in language instruction. Through a comprehensive review, the article aims to provide educators with insights into effective practices that enhance language learning experiences for young learners.